Pengaruh Tarif Pengiriman, Kualitas Pelayanan, Dan Ketepatan Waktu Terhadap Kepuasan Pelanggan Pengguna Jasa PT. Citra Van Titipan Kilat (TIKI) Semarang - Utomo, Wahyu Tri; Putra, Febrianur Ibnu Fitroh Sukono (P3M Universitas Aisyiyah Surakarta, 2024)
Customer satisfaction is a feeling of customers, whether in the form of pleasure or a feeling of customer disappointment arising from comparing the appearance of a product which will be related to the customer's expectations for that product. This research aims to determine the effect of shipping rates, service quality and timeliness on customer satisfaction using PT. Citra Van Titipan Kilat (TIKI) in Semarang. The research method used is quantitative and uses primary data in the form of a questionnaire. The population used is customers using PT delivery services. Citra Van Titipan Kilat (TIKI) in all parts of Semarang City which has been used at least 2 times. The sample used was 104 respondents, using purposive sampling technique. The analysis method uses multiple regression analysis with the SPSS application. The results of this research show that each variable, shipping rates, service quality, and timeliness have a positive and significant effect on customer satisfaction.